PENYULUHAN BAGI IBU-IBU PENGGERAK EKONOMI PRODUKTIF RINTISAN DI KECAMATAN DAHA UTARA - Titien Agustina; Sulaiman Sulaiman; Muhammad Rudiansyah; Nurhikmah Nurhikmah; Maulana Maulana; Alfiannor Alfiannor; M. Rio Mursid Wijaya; Chumaidi Chumaidi (Bakti Banua : Jurnal Pengabdian Kepada Masyarakat, 2020)
Human resource development in the home industry sector is mostly done by human resources with limited resources but have the will to be able to produce and have an impact on family and community economic resources. Mothers who are pioneers of productive economy in this pioneering are generally still weak in their capacity and capability in developing business, both in terms of business management in general, financial management, production management, marketing management, to human resource management itself in order to explore the deepest potential possessed. Through counseling activities become one of the efforts to help enlighten, add knowledge and insight and skills, so that intelligence grows in doing something and produces what is desired, even giving birth to creativity and innovation at a later stage.Human resource development in the home industry sector is mostly done by human resources with limited resources but have the will to be able to produce and have an impact on family and community economic resources. Mothers who are pioneers of productive economy in this pioneering are generally still weak in their capacity and capability in developing business, both in terms of business management in general, financial management, production management, marketing management, to human resource management itself in order to explore the deepest potential possessed. Through counseling activities become one of the efforts to help enlighten, add knowledge and insight and skills, so that intelligence grows in doing something and produces what is desired, even giving birth to creativity and innovation at a later stage.